Cobras retóricas, horror poético: efeitos de expressão e a morte de Laocoonte na Eneida - Thamos, Márcio [UNESP] (My University, 2017)
In an analysis on the episode of Laocoon's death, inserted into the account of the Trojan horse, in the Aeneid, we highlight certain meaning effects achieved from the use of some rhetorical figures. In the examples, hyperbaton, alliteration, assonance and anaphora give iconicity contour to the verses; and a rare simile is used as narrative sequence feature, with diegetic function. The simple use of these figures could not provide the text with such a high degree of expressiveness. This leads to a reflection upon the need to always take into account the interpenetration of the planes of language and the solidarity between content and expression as an index of literariness. To contextualize the episode, I offer a decasyllable translation of Virgil's hexameters. This translation seeks to preserve the figures of speech used in Latin and the main meaning effects raised by them.
Rhetorical snakes, poetic horror: Expression effects and the death of Laocoon in the Aeneid
Keywords: Content and expression; Meaning effects; Rhetorical figures; Trojan horse; Virgil